Self-organized biological dynamics and nonlinear control : toward understanding complexity, chaos and emergent function in living systems - Walleczek, Jan, 1964- (Cambridge University Press, 2000)
The growing impact of nonlinear science on biology and medicine is fundamentally changing our view of living organisms and disease processes. This book introduces the application to biomedicine of a broad range of interdisciplinary concepts from nonlinear dynamics, such as self-organization, complexity, coherence, stochastic resonance, fractals, and chaos.